Neoadjuvant treatment patterns and biomarker selection in muscle-invasive bladder cancer - Wei He; Jiaxin Xie; Ziwei Wang; Maoyu Wang; Qing Chen; Chen Zhang; Yue Wang; Xufeng Yu; Yi Wang; Hui Zhang; Xuncheng Yang; Zhensheng Zhang; et al. (Discover Oncology)
Abstract As the feasibility of risk-adaptive bladder-sparing treatment is increasingly validated, the prospects for neoadjuvant therapy in muscle-invasive bladder cancer (MIBC) are rapidly evolving. For patients seeking effective and tolerable treatment options, platinum-based chemotherapy, particularly dose-dense MVAC (ddMVAC), remains the preferred standard. However, the emergence of novel interventions such as immune checkpoint inhibitors (ICIs), FGFR inhibitors, and antibody–drug conjugates (ADCs) offers promising alternatives, especially for those ineligible for cisplatin-based regimens. Ongoing clinical trials, including KEYNOTE-B15, RC48-C017, and NIAGARA, are actively investigating the efficacy of combining these agents with existing neoadjuvant therapies, aiming to establish new first-line treatment options. Although predictive models based on histological features, DNA damage repair (DDR) genes, molecular subtyping, liquid biopsies, and in vitro organoids have demonstrated potential in guiding treatment selection, the clinical translation process remains slow. There is a pressing need to accelerate the exploration of genetic heterogeneity in MIBC and to validate the clinical utility of emerging biomarkers to optimize patient selection for neoadjuvant therapy. This review will comprehensively examine the evolution of neoadjuvant treatment paradigms, focusing on high-quality evidence from evidence-based medicine and translational clinical research, with the aim of enhancing and updating readers' knowledge of neoadjuvant therapy for MIBC and providing insights for future practice and research directions.